Identification and characterisation of proteases in Mycobacterium tuberculosis - Dave, Joel Alex (Division of Medical Biochemistry and Structural Biology, 2018)
Virulence determinants of M. tuberculosis remain largely unknown. Of key interest has been the ability of the bacterium to survive intracellularly within its host cell, the macrophage, and its ability to cause extensive tissue necrosis. Exported proteases are commonly associated with virulence in bacterial pathogens, yet their role in Mycobacterium tuberculosis has virtually not been studied. Preliminary experiments showed M. tuberculosis culture filtrates contained a proteolytic activity inhibited by mixed serine/cysteine protease inhibitors and activated by Ca²⁺, features typical of some serine proteases, notably subtilisins, and possibly metalloproteases. Purification attempts were unsuccessful. A family of five genes that encode putative, secreted, serine proteases has recently been described in M. tuberculosis. These proteases share 36-47% sequence identity and are all encoded with putative signal peptides, suggesting that they are translocated across the cytoplasmic membrane. One member, mycP1, was selected for further study. The gene product, mycosin-1, was 30-35% identical to bacterial subtilisin-like serine proteases and contained the classic catalytic triad and oxyanion hole. Mycosin-1 also contained a typical signal peptide, a likely propeptide, and a Cterminal hydrophobic sequence with a high transmembrane potential. Topology analyses predicted mycosin-1 to be a type I ectoprotein. Consistent with this, expression of mycosin-1 in M. tuberculosis and in Mycobacterium smegmatis transformed with mycP1 (M. smegmatis-P1) was limited strictly to the cell envelope, as seen by Western blotting, and immunogold electron microscopy. Only full-length, 50-kDa mycosin-1 was observed by Western blotting in broth-grown M. tuberculosis and M. smegmatis-P1 lysates, whereas a 40-kDa species was detected in 6-week M. tuberculosis culture filtrates. A similar 40-kDa immunoreactive band was also observed in lysates of macrophages infected with M. tuberculosis, consistent with robust transcription of the mycP 1 gene during growth in macrophages. Since putative mature mycosin-1 has a molecular weight of 38.6 kDa, the 40-kDa protein may represent activated mycosin-1 after propeptide cleavage. In conclusion, mycosin-1 is an exported, cell envelopeassociated subtilisin homolog that is expressed during growth of M. tuberculosis in vitro and in macrophages.